Analysis of flexible fabric structures - Pimm, Andrew James (2011)
This thesis is primarily aimed at carrying out analysis of Energy Bags, reinforced fabric bags used for subsea compressed air energy storage. Subsea compressed air energy storage is a completely new method of large-scale energy storage designed to be integrated with direct-compression offshore wind turbines and wave energy converters. Energy Bags are impermeable bags anchored to the seabed at significant depths (e.g. 500m) in which high pressure air, compressed by specially designed wind turbines and wave energy converters, is stored at pressures roughly equal to the hydrostatic pressure of the surrounding water. Energy Bags do not need to be particularly strong because most of the reaction to the pressure load is provided by the surrounding water, and high energy densities are available at such depths as 500m.